Distant blunt forceps dissection in tissue expander insertion: a novel technique. Issue 3 (August 2016) - Weissman, Oren; Hundeshagen, Gabriel; Bank, Jonathan; Zilinsky, Isaac; Solomon, Efrat; Remer, Eric; Rasner, Guy; Haik, Josef
Tissue expansion using implantable expanders is a useful means of generating surplus tissue for reconstruction of defects such as scarring following burns. The authors describe their technique of incisions distant to the desired location of expander placement, and remote dissection of the expander pocket with hydrodissection and blunt forceps. A total of 81 expanders were placed in 30 consecutive patients, 81% of whom had burn scars due for reconstruction. During preparation, no complications, such as bleeding, were encountered, except one case with severe subdermal fibrosis, in which bleeding was stopped through brief application of pressure. Postoperatively, no complications were encountered in 76% of patients; however, 16.6% exhibited surgical site infection, which was managed conservatively and was correlated with a high number of expanders implanted at once. One patient experienced hematoma formation that resolved spontaneously, and one instance of expander extrusion and subsequent removal occurred. Receiving ≥2 expanders at the same time was statistically associated with higher risk for complication(s). The authors' complication rates were moderate and comparable with open or endoscopic approaches. Time of expansion is reduced compared with the open approach due to distant incision placement and immediate usability. Cost effectiveness appeared to be better using only inexpensive forceps, rather than elaborate and costly endoscopic equipment.